Use of strain imaging to detect subtle myocardial involvement in post COVID-19 patients: An Indian perspective - Deepak Tomar; Aditya Kapoor; Zia Hashim; Kamlesh Raut; Arpita Katheria; Harshit Khare; Ankit Sahu; Roopali Khanna; Sudeep Kumar; Naveen Garg; Satyendra Tewari (Indian Heart Journal)
Background: The study assessed Global longitudinal strain imaging (GLS) to detect subtle myocardial dysfunction among patients clinically recovered from COVID-19. Methods: All patients (n = 101 76 % males, mean age 55.45 ± 11.14 years), and controls (n = 30), underwent clinical assessment and echocardiography, including GLS assessment. Results: The prevalence of diabetes mellitus, hypertension and dyslipidemia was comparable amongst patients and controls. The average GLS was significantly lesser in post COVID patients (−16.21 ± 1.96 vs −18.49 ± 1.64 respectively, p = 0.004) and significantly higher proportion of post COVID patients had GLS > -18 % (43 % vs 22.58 % respectively, p = 0.001) as compared to controls. The RV free wall longitudinal strain (RVFLS) was also lower in the patient group (22.35 ± 4.69 vs 24.19 ± 4.11, p = 0.004) and 21.7 % post COVID-19 patients had pathological RV FWLS (> −20 %) vs controls (6.6 %).Average GLS was significantly lesser in severe post COVID patients (viz −14.25 ± 1.92 vs −16.63 ± 1.61 vs −17.63 ± 1.91, p < 0.0001, respectively among severe, moderate and mild COVID-19 patients. On performing regression analysis, severity of COVID-19 (OR 7.762) was a significant predictor of impaired GLS. Conclusion: Despite normal global LVEF, post COVID-19 recovered patients had significantly lower LV GLS and RV FWLS with severe COVID-19 infection, regardless of having a clinical recovery. This study reiterates the importance of speckle tracking echocardiography as an important imaging modality for detection of subclinical myocardial dysfunction in the post COVID-19 recovered patients.